Molecular taxonomy of the guitarfish genus Acroteriobatus (Rhinopristiformes: Rhinobatidae) - Mia J. Groeneveld; Juliana D. Klein; Michaela van Staden; Rhett H. Bennett; Matthew L. Dicken; David A. Ebert; Bruce Q. Mann; Kashmika Perumal; Ralph G. A. Watson; Aletta E. Bester-van der Merwe (Marine Biodiversity, 2026)
Guitarfish species (genus Acroteriobatus ) display restricted distributions in undermanaged regions of intense fishing pressure. The importance of accurate specimen identification is well established, especially in the context of conservation management. However, guitarfishes remain poorly understood, which is exacerbated by taxonomic uncertainty due to morphological similarity. We therefore aimed (1) to identify molecular operational taxonomic units (MOTUs) within Acroteriobatus by analysing sampled specimens as well as publicly available sequence data for the cytochrome c oxidase subunit I ( COI ) and nicotinamide adenine dehydrogenase subunit 2 (ND2 ) genes, and (2) to augment and review the representation of these sequences on public databases. A molecular taxonomic approach integrating species delimitation and specimen assignment methods revealed 14 MOTUs. These MOTUs aligned with current species descriptions, displaying no evidence of cryptic diversity. Both genes demonstrated similar interspecific relationships that broadly reflected current distribution ranges, underscoring sub-regional endemism. Moreover, discrepancies in public sequence repositories were identified, attributed to misidentified specimens and the usage of outdated taxonomic nomenclature. Genetic diversity indices were substantially inflated when specimens were grouped based on reported species versus delimited MOTUs, thus overestimating genetic diversity. We highlight the need for extensive, curated DNA reference libraries, including revising earlier sequence entries in light of new taxonomic insights, to enable reliable identification of morphologically conserved species. The molecular resolution illustrated in this study can aid in clarifying taxonomic uncertainties in the genus Acroteriobatus .